The Influence of Work Motivation and Work-Life Balance on Job Satisfaction Among Generation Z Employees in DKI Jakarta - Eka Yulianti; Fetty Poerwita Sary (Eduvest - Journal of Universal Studies, 2025)
Generation Z has become a significant focus in the workforce, particularly in DKI Jakarta, which faces challenges with low job satisfaction among this group. This study aims to analyze the influence of work motivation and work-life balance on job satisfaction both partially and simultaneously. The research employed a quantitative method with a positivist approach, involving 165 respondents from Generation Z employees in DKI Jakarta. Data were collected using a questionnaire with a five-point Likert scale. The results show that work motivation (coefficient 0.486, p=0.000) and work-life balance (coefficient 0.464, p=0.000) significantly affect job satisfaction. These variables explain 40.2% of the variation in job satisfaction, with work flexibility and supportive workplace relationships as key factors. The study recommends strengthening motivation development programs and work-life balance policies to enhance employee balance and satisfaction among Generation Z. This study contributes new insights into how intrinsic and extrinsic factors jointly affect job satisfaction in a demographically distinct group. It recommends strengthening motivation development programs and implementing work-life balance policies to improve employee well-being and retention among Generation Z in urban settings.